Role of T-Cell Polarization and Inflammation and Their Modulation by n-3 Fatty Acids in Gestational Diabetes and Macrosomia - A. Hichami; O. Grissa; I. Mrizak; C. Benammar; N. A. Khan (Journal of Nutrition and Metabolism)
Th (T helper) cells are differentiated into either Th1 or Th2 phenotype. It is generally considered that Th1 phenotype is proinflammatory, whereas Th2 phenotype exerts anti-inflammatory or protective effects. Gestational diabetes mellitus (GDM) has been associated with a decreased Th1 phenotype, whereas macrosomia is marked with high expression of Th1 cytokines. Besides, these two pathological situations are marked with high concentrations of inflammatory mediators like tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6), known to play a pivotal role in insulin resistance. Dietary n-3 polyunsaturated fatty acids (n-3 PUFAs) may exert a beneficial effect by shifting Th1/Th2 balance to a Th2 phenotype and increasing insulin sensitivity. In this paper, we shed light on the role of T-cell malfunction that leads to an inflammatory and pathophysiological state, related to insulin resistance in GDM and macrosomia. We will also discuss the nutritional management of these pathologies by dietary n-3 polyunsaturated fatty acids (PUFAs).